The discourses of doing science in English - Revathi Ramiah,; Koo, Yew Lie; Jamilah Mustafa, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
In January 2003, Malaysia re-adopted the English language as a medium of instruction for science and mathematics. This change in the medium of instruction brings with it challenges of its own. What does it mean to 'do' science in the Malaysian context and to do so in English? How does the change in the medium of instruction from Bahasa Malaysia to English impinge upon current instructional and literacy practicesof teachers and learners? What kinds of change are required of the community that is invested in the teaching of science? This paper will address these questions by troubling some common-sense assumptions of 'doing' science in the Malaysian context in the light of findings of a qualitative case study conducted to investigate how one two teachers working in different contexts in a Malaysian school copes with the new medium of instruction and the myriad of issues that come with it.